Laboratory Innovation to Investigate Concrete Paving Blocks Compressive Strength - Riana H. Lumingkewas; Sigit P. Hadiwardoyo; Finno A. Hadiwardoyo (Civil Engineering Journal, 2023)
This research aims to evaluate the block method against the cube test method using variations in thickness. Paving blocks can be produced using a hydraulic machine or a simple press, and their performance can be measured based on density and compressive strength tests. The block test method shows that with the same material composition forming the paving block, a paving block with a higher thickness can lead to a lower compressive strength value. In contrast, the cube test method shows different results. The paving blocks used in this study had width and length sizes of 100 and 200 mm, respectively, and had varying heights of 60, 80, and 100 mm. The results reveal that the compressive strength of concrete paving blocks is more precise based on density. Furthermore, the empirical equation and conversion coefficient of the compressive strength of the block test to the cube test have been obtained. This empirical equation is highly recommended for the road pavement industry in controlling the quality of compressive strength, even when using block tests. Further research can help develop a formula for using additive materials in paving blocks. Doi: 10.28991/CEJ-2023-09-11-03 Full Text: PDF